PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM - Novitasari, Bunga; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Investment decision is an important issue and it is mostly encountered by investors. To invest in the capital market, investors require accurate information to find out how firm the correlation of the variables which become the cause of the fluctuation of the stock price of the company that will be bought by them.The samples are 18 manufacturing companies which are included basic industry and chemical sectors and the various industry sectors which are listed in the Investment Gallery of Indonesia Stock Exchange which is started from 2011 to 2013. The result of the research shows that the variable which has positive influence to the stock price is Net Profit Margin (NPM). Meanwhile, the other independent variables which are Return on Equity (ROE), Sales Growth (ÎSt), and Dividend Payout Ratio (DPR) have negative influence to the stock price.Keywords: Investor, Profitability, Sales Growth, Dividend Policy, Stock Price.